ANALISIS DAN IMPLEMENTASI RASPBERRY PI 3 MODEL B+ SEBAGAI SERVER E-LEARNING - Rahmat Widi Setiawan (Program Studi Teknik Informatika Universitas Nusa Putra, 2019)
Web server applications are usually run on high-specification hardware. This habit is due to the expectation that many requests will have to be handled simultaneously by the web server application so that it requires relatively large hardware to be able to serve well. For example, Processor i5 or i7 Gen3 or equivalent, 8 GB RAM, DDR3, 1 TB hard drive, Windows Server Operating System (64 Bit). But in the field most web server applications will not handle so many requests that they do not fully utilize the potential of the hardware they have. Therefore to build a server must first determine how heavy the activities to be performed by the server. Raspberry pi managed to become a Moodle E-Learning server as well as an access point, and was successfully implemented. Rasberry Pi can accommodate 5 users - 15 users simultaneously well. The quality of system performance can be measured by testing connectivity, QoS measurements include Throughput, Delay, Loss. Rasberry Pi access points are difficult to use when there are many wifi signals with the same channel around us, Interference. The use of new e-learning is filled with 2 subjects, which contains 50 multiple choice quiz modules and quiz modules.